(untitled) (American Journal of Islam and Society, 1992)
The era of Muslim rule in Spain (711-1491 CE) witnessed great contributions in many areas of knowledge and learning. Rapid strides were made in such diverse fields as art and architecture, agriculture and handicrafts, linguistics and literature, humanities and Social studies, music and poetry, and the physical and mechanical sciences. In fact, Islamic Spain, known to the Muslim world as al Andalus, served as a bridge for the transfer of the knowledge and wisdom of Classical Greece to Europe, a process that eventually led to the European Renaissance. The achievements of al Andalus will not be discussed in this paper. Rather, a survey of current research activities focusing on al Andalus will be presented. The areas covered are Europe, North America, North Africa, and parts of Asia. Latin American activities have not been surveyed due to the nonavailability of sources. Europe Europe has been the center of research on al Andalus. Various periodicals have served as major sources of information: Al-Andalus (Madrid 1933), Hesperis (Paris 1921-59), Hesperis-Tamuda (Rabat 1960), Miscellancea de Estudios Arabes y Hebraicos (Granda 1952), Revista de Instituto Egypcio de Studios Islamicos (Madrid 1953), Revue de la Occident Musulman et la Mediterranee (Aix-en-Provence 1966), Boletin de la Association Espaniola de Orientalistas (Madrid 1965), and Cuadernos de la Alhambra (Granada 1965). Certain important books have also appeared, such as Peres: la Poisie Andalousie, which includes a history of that period. Introductions to editions of texts and translations relate important infonnation about al Andalus under the al Murabitun and the al Mu’ahhidun dynasties. Hourani (1961) has written an excellent book: Averroes: On the Harmony of Religion and Philosophy. Memorial volumes in honor of E. Levi-Provencal, G. and W. Marcais, Menendes Pidal, Millas Vallicrosa y Parya, A. H. and R. Basset, H. A. R. Gibb and H. Wehr also contain much valuable data. Mention must be made of translations by institutes devoted to the study of al Andalus: Dar al Thaqafah (Beirut) has published valuable books, as have several Spanish and North African organizations (i.e., Conjeyo Superior de Investigaciones Cientificas Madrid], Instituto de Studios Islambs [Madrid], Institute des Haut-Etudes Marocaines Paris ...